La Descrittione di tutta Italia di Leandro Alberti e il Theatrum Orbis Terrarum di Abraham Ortelius - Gaiga, Silvia (Incontri. Rivista europea di studi italiani, 2014)
Leandro Alberti’s Descrittione di tutta Italia and Abraham Ortelius’ Theatrum Orbis Terrarum In her essay on the Italian sources informing Abraham Ortelius’ pioneering Theatrum Orbis Terrarum, Silvia Gaiga first demonstrates the enduring international impact of Leandro Alberti’s Descrittione di tutta Italia. Alberti’s chorography on the Italian peninsula quickly found a highly interested audience all over Europe, as is evidenced by its early presence in most of the academic libraries in Northern Europe. Its chorographic descriptions also informed an entrepreneurial cartographer like Abraham Ortelius when he conceived his ambitious atlas in the 1570s, a product closely linked to the emerging market of books targeting the growing group of travellers. Gaiga demonstrates that Ortelius appreciated Alberti’s suggestions particularly while addressing the erudite sections of this new audience. The versions of his atlas soon published in the vernacular, however, particularly in Dutch and German, include a radically different chorographic description of the Italian peninsula, produced by Ortelius personally and clearly directed at a kind of traveller interested in a more practical approach of his trip to Italy.